"I didn't have anything to decide, I wanted to help my kids"—An interview-based study of consent procedures for sampling human biological material for genetic research in rural Pakistan. Issue 3 (3rd July 2018) - Kongsholm, Nana Cecilie Halmsted; Lassen, Jesper; Sandøe, Peter
Abstract: Background: Individual, comprehensive, and written informed consent is broadly considered an ethical obligation in research involving the sampling of human material. In developing countries, however, local conditions, such as widespread illiteracy, low levels of education, and hierarchical social structures, complicate compliance with these standards. As a result, researchers may modify the consent process to secure participation. To evaluate the ethical status of such modified consent strategies it is necessary to assess the extent to which local practices accord with the values underlying informed consent.Methods: Over a 2-week period in April 2014 we conducted semistructured interviews with researchers from a genetic research institute in rural Pakistan and families who had given blood samples for their research. Interviews with researchers focused on the institute's requirements for consent, and the researchers' strategies for and experiences with obtaining consent in the field. Interviews with donors focused on their motivation for donating samples, their experience of consent and donation, and what factors were central in their decisions to give consent.Results: Researchers often reported modifications to consent procedures suited to the local context, standardly employing oral and elder consent, and tailoring information to the social education level of donor families. Central themes in donors' accounts of their decision to consent were the hope of getting something out of their participation and their remarkably high levels of trust in the researchers. Several donor accounts indicated a degree of confusion about participation and diagnosis, resulting in misconceived expectations of therapeutic benefits.Conclusions: We argue that while building and maintaining trusting relationships in research is important—not least in developing countries—strategies that serve this endeavor should be supplemented with efforts to ensure proper provision and understanding of relevant information, specifically about the nature of research and measures for individual consent and opt-out.